If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30x + -1(-1x + 6) + (-5x + 4) = -1(5x + 6) + (-8 + 30) Reorder the terms: 30x + -1(6 + -1x) + (-5x + 4) = -1(5x + 6) + (-8 + 30) 30x + (6 * -1 + -1x * -1) + (-5x + 4) = -1(5x + 6) + (-8 + 30) 30x + (-6 + 1x) + (-5x + 4) = -1(5x + 6) + (-8 + 30) Reorder the terms: 30x + -6 + 1x + (4 + -5x) = -1(5x + 6) + (-8 + 30) Remove parenthesis around (4 + -5x) 30x + -6 + 1x + 4 + -5x = -1(5x + 6) + (-8 + 30) Reorder the terms: -6 + 4 + 30x + 1x + -5x = -1(5x + 6) + (-8 + 30) Combine like terms: -6 + 4 = -2 -2 + 30x + 1x + -5x = -1(5x + 6) + (-8 + 30) Combine like terms: 30x + 1x = 31x -2 + 31x + -5x = -1(5x + 6) + (-8 + 30) Combine like terms: 31x + -5x = 26x -2 + 26x = -1(5x + 6) + (-8 + 30) Reorder the terms: -2 + 26x = -1(6 + 5x) + (-8 + 30) -2 + 26x = (6 * -1 + 5x * -1) + (-8 + 30) -2 + 26x = (-6 + -5x) + (-8 + 30) Combine like terms: -8 + 30 = 22 -2 + 26x = -6 + -5x + (22) -2 + 26x = -6 + -5x + 22 Reorder the terms: -2 + 26x = -6 + 22 + -5x Combine like terms: -6 + 22 = 16 -2 + 26x = 16 + -5x Solving -2 + 26x = 16 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -2 + 26x + 5x = 16 + -5x + 5x Combine like terms: 26x + 5x = 31x -2 + 31x = 16 + -5x + 5x Combine like terms: -5x + 5x = 0 -2 + 31x = 16 + 0 -2 + 31x = 16 Add '2' to each side of the equation. -2 + 2 + 31x = 16 + 2 Combine like terms: -2 + 2 = 0 0 + 31x = 16 + 2 31x = 16 + 2 Combine like terms: 16 + 2 = 18 31x = 18 Divide each side by '31'. x = 0.5806451613 Simplifying x = 0.5806451613
| X^2+4x-y-6=0 | | (2cos^2x-1)-cosx=0 | | 24b=6b | | 20*8= | | X+6(x+2)=3x-4 | | -8x+(-5x)=x | | (3k+2)(3k+2)=49 | | x^2+25x-4344=0 | | 2x^3y^3+3x^2y^2+4y=0 | | 10+4(-3)=x | | (7x-11)(3x-8)=0 | | 2/3+a-5/9=-a+2a | | X^2+y^2-10x-4y+20=0 | | 5-15s=8-16s | | 10-(-10)=x | | 3(v+2)+2v=7(v+1)+9 | | 6x+41+4x+39=180 | | x+y+14x-12y+4=0 | | x^2+19x+12=0 | | 7r-15=2r | | y=-2x^2+42+8 | | -4x-32=6(x+8) | | Y+3(y-6)=4y+2 | | 8x+-12+2x+2=180 | | 14=-5x+18 | | 12x-5x-3=0 | | 6x-5=9+2 | | 40+4y=y^2+4 | | X+20=9(x-4) | | (12-4i)(3+i)=0 | | c(ad)+x=bd+ad(yz) | | 5x^2=9x-5 |